Vilnius staging district during the Polish–Soviet War 1919–1920 - Roguski, Rafał (History / Istorija, 2019)
This paper has been developed based upon archive documents gathered at the “The Central Military Archives” in Warsaw, “The Border Guard Service Archives” in Szczecin, and the from the wider literature. The subject presented herein relates to the organisation of logistical support to the front line during the Polish–Soviet War 1919–1921, which so far has been described by researchers only to a minimal extent. In the first part of the article the author describes the system of the Polish civil administration in the territory of Lithuania. Then the author presents the military structures of the logistic support to the front line, i.e. a staging area. It describes the tasks of the Staging District (Vilnius Staging District Command Headquarters) and the lower levels of organisation to the rear of the front: staging prefectures /”prefecture stagings; in Poland ‘a powiat’ is an administrative unit lower than a province – translator’s note”/ and staging stations. The author acquaints the reader with the structure of “Staging Field Military Police, 22nd Voluntary Legion of Women and Vilnius Military Railway Guard Service”. The last segment of this paper describes the stage structures arrangement and functioning during 1920–1922, in the so-called Republic of Central Lithuania, that was created following the staged rebellion under the command of General Żeligowski.